The Effect of Reading Activity on Verbal Fluency in Older Adults - Herawati, Fitriana; Wiyono, Nanang; Munawaroh, Siti; Hastami, Yunia (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: The high prevalence of dementia affecting verbal fluency have been one of the global major concerns. Therefore, strategies to maintain or improve the verbal fluency in older adults is needed. Neuroplasticity-based program in the form of reading has been shown to affect the verbal fluency. Objective: This study aims to evaluate the effect of reading activity on verbal fluency in the older adults.Methods: This was a quasi-experimental study with pretest-posttest control group design. Thirty older adults were included. The inclusion criteria were more than 60 years of age, being to speak, being able to read, scores > 24, for the Mini-Mental State Examination (MMSE) score, having intention to fill out the reading habits questionnaire criteria. The exclusion criteria were the history of hypertension, diabetes mellitus, and psychiatric disorders, head trauma injury of neurological disorders, hearing loss and alcohol use. The patients were assigned into three groups: the control group (C-G), the 15-minute reading intervention group (G-15), and 30-minute reading intervention group (G-30). The reading aloud activity was given for 14 days. The verbal fluency was evaluated. Statistical analysis was performed using oneway ANOVA, Post Hoc, and paired T-test.Results: There were significant differences among groups in post-test phonemic score (p<0.05). post-test phonemic score in G-15 and G-30 increased significantly compared to that of pre-test phonemic score (p<0.05). Meanwhile, there were no significant difference in semantic score in all groups (p>0.05).Conclusion: The reading activity intervention for two weeks affects verbal fluency in older adults by increasing the phonemic score but not semantic score.